PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS SAK-EMKM DENGAN APLIKASI AKUNTANSI UKM - Novie Astuti Setianingsih; Wiwiek Kusumaning A; Atik Tri Andari; Elmi Rahma Aalin; Eti Putranti (Jurnal Abdi Insani, 2023)
Micro entrepreneurs have problems in compiling financial reports because business income is still mixed with household needs. This happens because of the lack of accounting knowledge and time constraints, activities are needed to assist the use of smartphone-based accounting applications with the SME Accounting application. The purpose of this community service activity is to provide training and assistance for partners regarding knowledge about making financial reports according to SAK-EMKM by using the UKM Accounting application. Training and assistance in preparing financial reports was carried out at the UMKM Cookies "Prima Rasa" in Ngasem District, Kediri Regency. Assistance will be carried out from 5 May 2021 to 5 June 2023. The methods that will be used in this community service are 1. Provide a basic understanding of business processes and the accounting cycle in a simple manner. 2. Explanation of various smartphone-based accounting applications and provides a more indepth introduction to the use of the SME Accounting application. 3. Provide training and assistance with accounting records directly using the SME Accounting application. The result of the implementation of this community service is to have a positive impact on UKM Kediri Prima Kediri Cookies, because in the past they could only record incoming and outgoing cash in a simple way, with this training assistance MSME actors can use the UKM Accounting application and can automatically compile reports finance.